2019
DOI: 10.1101/833707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR-based screens uncover determinants of immunotherapy response in Multiple Myeloma

Abstract: Cancer cells commonly develop resistance to immunotherapy by loss of antigen expression. Combinatorial treatments that increase levels of the target antigen on the surface of cancer cells have the potential to restore efficacy to immunotherapy. Here, we use our CRISPR interference and CRISPR activation-based functional genomics platform to systematically identify pathways controlling cell-surface expression of the multiple myeloma immunotherapy antigen - B cell maturation antigen, BCMA. We discovered that phar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
5
17
1
Order By: Relevance
“…This is in line with prior studies showing that sialic acids, present on the tumor cell surface, impair T-cellmediated tumor immunity (58). This study also showed that ICAM-1 expression is important for BCMA CAR T-cellmediated tumor cell lysis, whereas knockdown of genes belonging to the family of diacylglycerol kinases (DGK) increased sensitivity to BCMA CAR T cells (53).…”
Section: Reviewsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with prior studies showing that sialic acids, present on the tumor cell surface, impair T-cellmediated tumor immunity (58). This study also showed that ICAM-1 expression is important for BCMA CAR T-cellmediated tumor cell lysis, whereas knockdown of genes belonging to the family of diacylglycerol kinases (DGK) increased sensitivity to BCMA CAR T cells (53).…”
Section: Reviewsupporting
confidence: 91%
“…In addition, a CRISPR-based screen in an MM cell line identified several novel mechanisms that control the response to BCMA CAR T cells (53). Knockdown of genes in the sialic acid biosynthesis pathway sensitized MM cells to BCMA CAR T cells (53). This is in line with prior studies showing that sialic acids, present on the tumor cell surface, impair T-cellmediated tumor immunity (58).…”
Section: Reviewsupporting
confidence: 79%
See 2 more Smart Citations
“…For example, our group (45) and others (46)(47)(48) have used small molecules to increase expression of CD38 on myeloma plasma cells to enhance efficacy of daratumumab. Other examples include small molecule treatment to boost surface BCMA in myeloma (49,50) or CD22 in B-ALL (51). Furthermore, it has been suggested that acute responses to PI treatment, in particular marked chaperone upregulation and ER stress response, may translate into mechanisms of long-term cellular adaptation and resistance (52)(53)(54).…”
Section: Short Term Drug Treatment Leads To Divergent Surface Profilementioning
confidence: 99%